(Re)Turning to Motherhood and Academe: An Autoethnographic Account - Esnard, Talia (Journal of the Motherhood Initiative for Research and Community Involvement, 2016)
Women attempting to balance childcare with work of tenure-track academic positions continue to face many barriers related to the ambiguous nature of tenure and promotion policies, the lack of personal and professional support as well as persistent strains related to role conflicts that emerge from demanding academic schedules in higher education (Ward and Wolf-Wendel “Academic Motherhood: Managing Complex Roles”). Although a growing documentation of these processes and their consequences for academic mothers or mothers who are also academics do exist, narratives of the struggles, tensions and possibilities for overcoming these processes remain under-researched and not well understood. The objective of this article therefore is to explore the meanings, experiences, and challenges of academic motherhood and the ways in which these can be negotiated. Using an autoethnographic approach, the article delves into a critical reflection of the processes and dynamics that shape the contexts within which I return to academe after turning to motherhood a second time around. Reflections point to the socio-cultural and institutional bases of these strains and put forward viable and empowering ways in which can they be navigated.